Electronic datasheet parameter extractor and verifier system for printed circuit board development - Ma. Chalina S. Cuntapay; Mark Joseph B. Enojas; Hohn Lois C. Bongao (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Library components are composed of devices, symbols, and footprints which are the fundamental parts to design and develop printed circuit boards (PCB). In archiving PCB libraries, the creation and checking of the component’s parameters are very important. The checking of footprints and pin configurations from datasheets are manually done which causes delays and downtime when the components do not fit the developed PCB. It was found in a survey that 61.5% of errors come from footprints dimensions. These cause delays in the production and development of PCBs. In this study, a parameter extractor and verifier system were developed to mitigate the error of manual process of archiving library parameters from datasheets. Text recognition and pattern matching algorithms were used for the processing of images from datasheets. The 10-trial tests conducted for each footprint for the extraction of text from the cropped images for standard operating procedures (SOP) series and heat sink thin shrink small outline package (HTSSOP) series were found successful without any error. The checking of footprints and pin configuration was reduced from 45 minutes to 25 minutes. The developed system was evaluated based on user perception by 10 PCB library users which resulted to agree that the system is functional, efficient, and convenient to use.